POLITICAL DYNASTIES IN GOVERNMENT: A CASE STUDY OF NORTH PADANG LAWAS REGENCY GOVERNMENT - Akhirani, Riris Marito; H., Fatmariza (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
The purpose of this study is to analyze how the dynamics of the political dynasty of the harahap clan government in North Padang Lawas, and how the North Padang Lawas people's response to the system of government political dynasties formed in the district. This study uses a qualitative approach with a descriptive method. The informants in this study were selected using purposive sampling, namely by collecting accurate data or information related to the political dynasty of the North Padang Lawas government through individuals who are believed to have sources of accurate information related to research data. The results of this study indicate that the process of political dynasties in North Padang Lawas was formed due to several reasons. The first is from family relations (familism) obtained both in continguity and marriage. Second, political dynasties are formed through the popularity of prospective leaders. Third, political dynasties are formed from the experiences created by the leaders themselves in the previous period (the quality of leadership) that builds people's trust. Lastly, political dynasties could have been formed due to the influence of the demographic composition of the people who inhabit Paluta district itself, for example the domisioner clan (clan) that inhabited the district, namely the harahap clan. Furthermore, related to the problems above, the community responded with different views, namely positive sentiments and negative sentiments, including: a political dynasty can be a threat to us Indonesians, especially the North Padang Lawas district because it can endanger social mobilization and damage the regeneration of political journeys, as well as the occurrence of practical and dirty political practice.